Diversification patterns in the CES clade (Brassicaceae tribes Cremolobeae, Eudemeae, Schizopetaleae) in Andean South America - Salariato, Diego; Zuloaga, Fernando O.; Franzke, Andreas; Mummenhoff, Klaus; Al-Shehbaz, Ihsan A. (Botanical journal of the Linnean Society, 2016)
Dated molecular phylogenetic trees show that the Andean uplift had a major impact on South American biodiversity. For many Andean groups, accelerated diversification (radiation) has been documented. However, not all Andean lineages appear to have diversified following the model of rapid radiation, particularly in the central and southern Andes. Here, we investigated the diversification patterns for the largest South American-endemic lineage of Brassicaceae, composed of tribes Cremolobeae, Eudemeae and Schizopetaleae (CES clade).
Gesehen am 07.05.2020